Therapeutic Effects of Small-Particle Aerosols of Ribavirin on Parainfluenza (Sendai) Virus Infections of Mice - Larson, E. W. (1976)
Small-particle aerosol administration of ribavirin (1-β-d-ribofuranosyl-1,2,4-triazole-3-carboxamide) increased survival rates, extended the time to death, delayed lung pathology, and reduced pulmonary virus levels in Sendai virus-infected mice.